Word meaning types acquired before vs. after age 5: implications for education - Biemiller, Andrew (Frontiers in Psychology, 2024)
This article concerns two types of word meanings: nonverbal meanings which appear to be associated with neurological representations and verbally-based meanings which appear to depend in part on other words to construct meanings. Using word use data from Hart & Risley’s study of children aged 19 to 36 months, and word meaning knowledge data from Biemiller and Slonim’s studies of children between aged 5 to 11, meanings were classified as nonverbal or verbally-based. Biemiller and Slonim used sampled word meanings reported known from grade levels 2 to 12 reported by Dale and O’Rourke in their Living Word Vocabulary. Virtually all meanings used at age 3 or known at age 5 (preschool) were classified nonverbal. By grade two, and even more by grade five, children had added many verbally-defined meanings, although by grade five the majority of the word meanings known were still nonverbal. Evidence for neurological meaning associates are cited. Implications for vocabulary support and instruction at various ages suggest that for children under 6, supporting larger nonverbal vocabularies while after age 6 should prioritize verbally-defined meanings.